A feminist rethinking of drama therapy: The role of audience and aesthetics in Cancer As Change Maker. Issue 2 (1st October 2015) - Alker, Gwendolyn
In this article historical themes and methods of feminist performance are invoked to analyse a specific case study: Cancer As Change Maker, a piece of drama therapy created at New York University in 2013. Through this example, the author engages with the perils and potential lessons that feminist theatre carry for therapeutic theatre with a particular focus on the role of aesthetics and audience engagement.